Malaysian tax policy and corporate tax burdens : an industry analysis / Rohaya Md Noor, Nor'Azam Mastuki and Barjoyai Bardai - Md Noor, Rohaya; Mastuki, Nor'Azam; Bardai, Barjoyai (Universiti Teknologi MARA, Shah Alam, 2009)
This study examines corporate income tax burdens, specifically known as corporate effective tax rates (ETRs) of Malaysian listed companies during the new tax regime. The Malaysian tax system had undertaken a major tax reform whereby corporate taxpayers are subject to the current year assessment and self assessment system, effective from the year 2000 and 2001 respectively. Thus, the goal of this study is to compare the tax rate effectively experienced by each company within and across the sectors, with the corporate statutory tax rate (STR) or official tax rate (OTR) for the financial years from 2000 to 2004. Corporate ETRs take into consideration the tax reductions that resulted from special tax provisions, such as, changes in tax laws and tax incentives which cause corporate ETRs to diverge from the STR. Using a micro-backward looking approach from a sample of 3432 firm-years of Malaysian public listed companies from ten sectors, the study found variability of corporate ETRs between companies in the same sector and also across sectors. The statistical results provided evidence that the average ETR for all sectors fall below the STR of 28%. The study found that companies from hotel sector experienced lowest ETRs with an average ETR of 9%. Meanwhile, companies from construction sector experienced highest ETRs with an average ETR of 26%. The divergence of corporate ETRs from the STR ranged from 2% to 19% during the period 2000 to 2004. The difference between corporate ETRs and the STR provides evidence on the pervasiveness of tax incentives provided by the government to certain selected activities or industries. Hence, the variability of corporate ETRs implied that the equity and neutrality principles of the present tax system are being challenged.